Developing a framework for sustainability governance in the European Union (2005)
Sustainable development represents a major governance challenge of the 21st century. If societal development trajectories are to be realigned on to more sustainable pathways major changes will be required to existing processes and practices of governance. This essay considers the nature of these changes and discusses implications for social science research.